Pharmacy QR code / Siti Khairul Niza Sukri ... [et al.] - Sukri, Siti Khairul Niza; Elias, Shamsul Jamel; Che Sidik, Noreha; Yusni, Nurul Fatina; Mohd Zaim, Nur Farah Hanani (Universiti Teknologi MARA, Kedah, 2019)
The objectives of this project is to provide the most efficient way to provide the information of medicine prescribed to the patient. Pharmacy QR Code is implement as each medicine has its own unique identifier which are represent with their own QR code design. Cellular technology and satellite communication had increased communication speeds and made ‘connecting' easier. Pharmacy QR code is a simplest way for the patient to know about the medication taken as they just only need to scan using QR Application from their smartphone and within seconds they can obtain the details. Communication is rapid, travel is fast, movement is easy, action is quick, interaction has speed up and so has life. Things that once took hours to complete, can be done in seconds today. The QR code provide the information very quickly and precisely about the medicine’s detail such as the content, dosage, indications, contraindications, special precaution and adverse reaction. Material Safety Data Sheet (MSDS) that provide information on the potential hazards can be replaced by QR Code and this is a potential value for commercialization as the project can be introduce and implement to a pharmacy and medicine manufacturer. By implementing this project pharmacy QR code, huge resources and cost can be save up as it uses less number of paper to provide information about medicines to patients. This system is cost effective in terms of time, manpower and material usage as it was operated online.